Ferrocene-based dendritic macromolecules as efficient supports in nanocatalysis. (19th April 2022) - Wang, Wenjuan; Ornelas, Catia; Diallo, Abdou K.; Deraedt, Christophe; Wang, Yanlan; Lu, Feng; Gu, Haibin; Astruc, Didier
Abstract: This mini-review highlights results on nanocatalysis involving various ferrocene-containing macromolecular supports (arene-cored and Pd-nanoparticle-cored dendrimers and dendronized polymers) obtained in our research group during the last 15 years. Nanocatalysis with Pd and Au nanoparticles stabilized by these metallomacromolecules have shown excellent catalyst efficiency and recyclability in very low amounts for C–C cross-coupling reactions, olefin hydrogenation and 4-nitrophenol reduction. The ferrocene group plays a crucial role in these dendritic supports with its redox activity and tridimensionality blocking nanoparticle escape. Graphical abstract: Image 1 Highlights: Ferrocene-ended macromolecular supports for nanocatalysis are reviewed. Efficient nanocatalysts are stabilized by triazolylferrocene-ended macromolecules. Redox and tridimentional ferrocene properties are crucial for nanocatalyst supports.